A review of silvopastoral systems in native forests of Nothofagus antarctica in southern Patagonia, Argentina - Peri, Pablo Luis (2016)
Silvopastoral systems in Nothofagus antarctica (ñire) forest have become an economical, ecological and productive alternative in Patagonia. Southern Patagonia’s experience over the past 12 years with silvopastoral systems is reviewed. The productivity and nutritive value (crude protein content and dry matter digestibility) of the understorey grassland were dependent on the interaction of environmental (mainly soil water availability and light intensity) and management factors under the trees and in turn determined animal performance. A method developed for carrying capacity estimation at the paddock level was based on the potential aboveground net primary production, and values ranged from 85 to 2200 kg DM ha−1 year−1. Planned thinning in secondary forest stands provides wood production and also improves the undestorey DM production by increasing incoming radiation. Within a management plan, a stand’s water stress conditions as well as the use of Reineke’s stand density index are proposed to assist in determining thinning intensities. Livestock production is the main annual income of silvopastoral systems where cattle and mixed livestock production (cattle + sheep) is the main activity. Animal performance at the whole farm scale is presented by comparing traditional extensive grazing management with an adaptive silvopastoral management that included strategic separation in homogeneous areas (grass steppe, forest and riparian meadows), stocking rate adjustment to grassland net primary production and the protection of regeneration from herbivores browsing. Data from litter decomposition, nutrient cycling and carbon storage studies also are presented. Finally, aspects related to the criteria and indicators to assess ñire forest’s sustainability under silvopastoral use along with biodiversity conservation issues are presented.